2014
DOI: 10.1021/am501911y
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Selective Dependence of Room Temperature Ferromagnetism Induced by Hierarchical ZnO Nanostructures

Abstract: We report on the room temperature ferromagnetism of various highly crystalline zinc oxide (ZnO) nanostructures, such as hexagonally shaped nanorods, nanocups, nanosamoosas, nanoplatelets, and hierarchical nano "flower-like" structures. These materials were synthesized in a shape-selective manner using simple microwave assisted hydrothermal synthesis. Thermogravimetric analyses demonstrated the as-synthesized ZnO nanostructures to be stable and of high purity. Structural analyses showed that the ZnO nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(54 citation statements)
references
References 72 publications
(139 reference statements)
6
46
0
1
Order By: Relevance
“…The origin of the green PL emission, as the most commonly observed defect emission in ZnO nanostructures, is quite controversial. In the recent studies (Ghosh et al 2013;Motaung et al 2014;Panigrahy et al 2010), this emission is associated with singly ionized oxygen vacancies V O ? and/or zinc vacancies V Zn , located mainly on the ZnO surface.…”
Section: Pl Spectroscopy Analysismentioning
confidence: 94%
“…The origin of the green PL emission, as the most commonly observed defect emission in ZnO nanostructures, is quite controversial. In the recent studies (Ghosh et al 2013;Motaung et al 2014;Panigrahy et al 2010), this emission is associated with singly ionized oxygen vacancies V O ? and/or zinc vacancies V Zn , located mainly on the ZnO surface.…”
Section: Pl Spectroscopy Analysismentioning
confidence: 94%
“…The observed RTFM is thought to be due to higher V O on the TiO 2 NPs surface (see PL results) and structure defect induced by milling process which result in coalescence of ferromagnetic domains [43] such as reduced crystallites size (see Table 1). Previous studies [9,[44][45][46] showed that larger crystals are detrimental to magnetic properties. Moreover, the origin of ferromagnetism for TiO 2 NPs diluted magnetic semiconductors can be explained by various carrier mediated mechanisms that include double-exchange, super-exchange or Ruderman-Kittel-Kasuya-Yosida (RKKY) exchange interactions [43].…”
Section: Milling Time (H)mentioning
confidence: 95%
“…The detected carbon is associated to the carbon tape used during the measurements and that adsorbed on the surface during the exposure of the sample to the ambient atmosphere. The binding energy for the C1s peak at 284.6 eV was used as the reference for calibration [9]. Fig.…”
Section: Milling Time (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows the ESR spectra of undoped and Mgdoped ZnO nanoparticles. A broad resonance signal has been observed for undoped ZnO nanoparticles which can be attributed to long-range ferromagnetic ordering between the electrons trapped in oxygen vacancies [17]. Generally, ZnO loose oxygen resulting in formation of oxygen vacancies, owing to its low formation energy (3.8 eV).…”
Section: Xrd Analysismentioning
confidence: 99%